2014
DOI: 10.1016/j.jnci.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

When would we advocate a total thyroidectomy in cases of hypopharyngeal carcinoma?

Abstract: We would advocate a total thyroidectomy in cases of advanced stages of hypopharyngeal carcinoma, bilateral tumors, postcricoid carcinoma and in all patients with definite radiological evidence of thyroid gland invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The researchers concluded that routine thyroid resection in larynx cancers should be limited to cases of subglottic or transglobic involvement (3). They recommended thyroidectomy in cases of bilateral tumors, high staging, postcricoid involvement, and clear radiological evidence (5) or in the event of muscle involvement or in case of subglottic involvement of more than 10 mm (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers concluded that routine thyroid resection in larynx cancers should be limited to cases of subglottic or transglobic involvement (3). They recommended thyroidectomy in cases of bilateral tumors, high staging, postcricoid involvement, and clear radiological evidence (5) or in the event of muscle involvement or in case of subglottic involvement of more than 10 mm (7).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of thyroid gland involvement in larynx and hypopharynx cancers has been reported from 5% to 30% in various studies (3)(4)(5)(6)(7)(8). There are no clear vascular and lymphatic linkages between the thyroid gland and larynx, and most researchers agree that thyroid involvement in the larynx and hypopharynx cancers could occur only through local invasion (5)(6)(7)(8)(9). The major risk factors for thyroid gland involvement in larynx cancers are laryngeal cartilage involvement, extensive subglottic, and transglottic involvement (5-7), but the degree of tumor differentiation effect on thyroid gland involvement and invasion is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other malignant epithelial tumors of the head and neck area, hypopharyngeal cancer has a very poor prognosis irrespective of the therapeutic regimen instituted; because of the late presentation, tendency to submucosal extension into the esophagus, lack of anatomical barriers of the hypopharyngeal wall and early metastases to regional lymphatic nodes of the neck, as well as a higher incidence of distant metastases3.An extended resection to achieve radicality is therefore mandatory and safe macroscopic margin is considered 4 .…”
Section: Introductionmentioning
confidence: 99%